2018
DOI: 10.1016/j.neuroimage.2017.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Human in-vivo brain magnetic resonance current density imaging (MRCDI)

Abstract: Magnetic resonance current density imaging (MRCDI) and MR electrical impedance tomography (MREIT) are two emerging modalities, which combine weak time-varying currents injected via surface electrodes with magnetic resonance imaging (MRI) to acquire information about the current flow and ohmic conductivity distribution at high spatial resolution. The injected current flow creates a magnetic field in the head, and the component of the induced magnetic field ΔB parallel to the main scanner field causes small shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(124 citation statements)
references
References 52 publications
4
120
0
Order By: Relevance
“…This non-invasive method allows to directly validate the simulated electric field, based on human in vivo measurements. First results indicate that FEM models yield a reasonable approximation to the measured electric fields (Göksu et al, 2018). Additionally, estimated electric fields from specific FEM head models showed a good correspondence when compared to intracranial recordings from human patients Lafon et al, 2017) and non-human primates (Kar et al, 2017;Opitz et al, 2016).…”
Section: The Role Of Targeted Tes For Physiologically Effective Stimumentioning
confidence: 78%
See 2 more Smart Citations
“…This non-invasive method allows to directly validate the simulated electric field, based on human in vivo measurements. First results indicate that FEM models yield a reasonable approximation to the measured electric fields (Göksu et al, 2018). Additionally, estimated electric fields from specific FEM head models showed a good correspondence when compared to intracranial recordings from human patients Lafon et al, 2017) and non-human primates (Kar et al, 2017;Opitz et al, 2016).…”
Section: The Role Of Targeted Tes For Physiologically Effective Stimumentioning
confidence: 78%
“…Additionally, estimated electric fields from specific FEM head models showed a good correspondence when compared to intracranial recordings from human patients Lafon et al, 2017) and non-human primates (Kar et al, 2017;Opitz et al, 2016). The observed modeling errors in these studies were mostly attributed to tissue conductivities (Göksu et al, 2018;Huang et al, 2017). In the large body of FEM applications these are not adapted to individually varying conductivity values and thus might lead to errors in the estimation of intracranial current densities induced by tES Schmidt et al, 2015).…”
Section: The Role Of Targeted Tes For Physiologically Effective Stimumentioning
confidence: 87%
See 1 more Smart Citation
“…Since our initial work, two additional promising techniques have been proposed. Utilizing Magnetic Resonance Electrical Impedance Tomography (MREIT) (Kasinadhuni et al, 2017;Goksu et al, 2018), these techniques utilize alternating currents to map current-induced magnetic fields (along Bz). The published studies derived current-density distributions under the assumption of zero current density in one direction.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, (Opitz et al, 2018) found underestimated fields in one of the studied patients, while the calculated e-fields were too high in the second patient. Recently, (Göksu et al, 2018) demonstrated a novel non-invasive approach to reconstruct TES induced current densities in the brain from magnetic resonance images of the currentgenerated magnetic fields (magnetic resonance current density imaging, MRCDI). They present initial results on five subjects showing good agreement between simulated and measured current densities, with a moderate but systematic underestimation of the current densities by the models based on "standard" ohmic conductivities.…”
Section: Introductionmentioning
confidence: 99%